Inequality, information technology and inclusive education in Sub-Saharan Africa - Simplice Asongu; Stella-Maris I. Orim; Rexon T. Nting (African Governance and Development Institute (AGDI), 2019)
This study examines linkages between inequality, information and communication technology (ICT) and inclusive education in order to establish inequality thresholds that should not be exceeded in order for ICT to promote inclusive education in 42 countries in sub-Saharan Africa for the period 2004-2014. The empirical evidence is based on the Generalized Method of Moments. The following findings are established. First, a Gini coefficient and an Atkinson index of respectively, 0.400 and 0.625 are income inequality thresholds that should not be exceeded in order for internet penetration to positively influence inclusive education. Second, a Gini coefficient, an Atkinson index and a Palma ratio of respectively, 0.574, 0.676 and 9.000 are thresholds of income inequality that if exceeded, fixed broadband subscriptions will no longer positively affect inclusive education. As a main policy implication, the established inequality thresholds should not be exceeded in order for ICT to promote inclusive education in sampled countries. Other implications in the light of Sustainable Development Goals (SDGs) are discussed.
Keywords: I24; I25; I39; O40; O55; 330; Education; Inequality; ICT; Sub-Saharan Africa